11/12х - 2/3 = - 5/10 - 3/4х
11/12х + 3/4х = 2/3 - 1/2
11/12х + 9/12х = 4/6 - 3/6
20/12х = 1/6
х = 1/6 : 20/12
х = 2/20 = 1/10 = 0,1
х = 0,1
- 0,5 = - 5/10: - 5/10 = - 1/2
ответ:X=10
Пошаговое объяснение:
11/12x-2/3=-0,5-3/4x. /12
11x-8=-6-9x
11x+9x=-6+8
20x=2
X=20:2
X=10
11/12х - 2/3 = - 5/10 - 3/4х
11/12х + 3/4х = 2/3 - 1/2
11/12х + 9/12х = 4/6 - 3/6
20/12х = 1/6
х = 1/6 : 20/12
х = 2/20 = 1/10 = 0,1
х = 0,1
- 0,5 = - 5/10: - 5/10 = - 1/2
ответ:X=10
Пошаговое объяснение:
11/12x-2/3=-0,5-3/4x. /12
11x-8=-6-9x
11x+9x=-6+8
20x=2
X=20:2
X=10